Clinical outcome following lung transplantation in patients with cystic fibrosis colonised with Burkholderia cepacia complex: results from two French centres. Issue 8 (11th April 2008) - Boussaud, V; Guillemain, R; Grenet, D; Coley, N; Souilamas, R; Bonnette, P; Stern, M
Abstract : Background: Infection with Burkholderia cepacia complex (BCC) is a life threatening complication of cystic fibrosis (CF), often seen as a contraindication for lung transplantation. Methods: A long term retrospective study was conducted of all patients with CF undergoing lung transplants from January 1990 to October 2006 in two French centres allowing transplantation in patients colonised with BCC. Results: 22 of the 247 lung transplant patients with CF were infected with BCC ( B cenocepacia genomovar III (n = 8), B multivorans genomovar II (n = 11), B vietnamiensis genomovar V (n = 2) and B stabilis genomovar IV (n = 1)). BCC colonisation was not associated with any significant excess mortality (HR 1.5, 95% CI 0.7 to 3.2; p = 0.58). However, early mortality rates tended to be higher in the BCC group than in the non-BCC group (3 month survival: 85% vs 95%, respectively; log rank p = 0.05). Univariate analysis showed that the risk of death was significantly higher for the eight patients infected with B cenocepacia than for the other 14 colonised patients (HR 3.2, 95% CI 1.1 to 5.9; p = 0.04). None of the other risk factors tested—primary graft failure, late extubation, septicaemia—had a significant effect. The 5 year cumulative incidence rate of bronchiolitis obliterans syndrome was not significantly higher in the BCC group than in the non-BCC group (38% vs 24%, respectively; p = 0.35). Conclusion: Our results suggest that BCC infection with a non-genomovar III organism may not be associated with excess mortality after lung transplantation in patients with CF and should not be seen as sufficient reason to exclude lung transplantation. However, colonisation with B cenocepacia remains potentially detrimental.